The Impact of Human Resource Digitalization through HRIS on Human Resource Management Efficiency: A Technology Acceptance Model Approach - Jufrina Mandulangi (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Digital transformation in the field of Human Resources, particularly through the implementation of Human Resource Information Systems (HRIS) or Digital HR, has emerged as a prominent global trend as organizations seek to enhance efficiency and responsiveness in managing human capital. Although HRIS adoption has become increasingly widespread across sectors, systematic empirical evidence explaining how such digitalization affects the operational efficiency of HR management remains limited, especially when viewed across diverse organizational contexts. This gap highlights the need for theoretically grounded studies that not only measure efficiency outcomes but also consider user acceptance as a critical determinant of successful implementation. This study examines the impact of HRIS implementation on HR management efficiency by employing the Technology Acceptance Model (TAM) as its theoretical framework, with particular attention to perceived ease of use and perceived usefulness. Using a quantitative approach, data were collected through questionnaires distributed to 250 HR professionals from various industry sectors who had been using HRIS for a minimum of one year. The data were analyzed using Structural Equation Modeling with Partial Least Squares to assess the relationships among key variables. The results indicate that both perceived ease of use and perceived usefulness significantly shape attitudes toward HRIS utilization, which in turn exert a positive and significant influence on HR management efficiency. The efficiency gains are most evident in administrative processes, recruitment activities, employee data management, and reporting functions. Overall, the findings demonstrate that successful HRIS implementation, supported by strong user acceptance, can substantially enhance the operational efficiency of HR departments. This study not only reinforces the continued relevance of TAM in the context of HR technology adoption but also offers practical insights for organizations seeking to optimize the returns on their digital HR investments.